Implementação de Sistemas de Gestão para Projetos - Neves, Rodrigo Barbosa (2004)
The Project Management is becoming an important tool for companies, where they need improvement in a competitive environment, that makes the goals of projects harder to reach, and the management need to improve to make it. Many companies as looking for to implement project management by management systems such as Project Management Office and Maturity Models, but this has shown to be a tough path with so many difficulties, and some times affords in project management area has fail or become extremely expensive to reach their goals. So, using a bibliographical research and studies about project management, organizational structures, and the human factor in this context, adding interviews about this subjects made in Colleges and Project Management Groups, it searches for answers about which, why and how this difficulties to implement project management systems occurs. In a management system constituted by Methodologies, IT Systems a People, this study shows the importance o the human factor on project management success and to the success o project management systems implementations, when cultural changes, resistance to change and people management are sub estimated, but the consequences are to expensive and materialized in project management systems that fail to reach their goals.